The Relationship between Ethnic Classroom Composition and Turkish-Origin and German Students' Reading Performance and Sense of Belonging - Mok, Sog Yee; Martiny, Sarah E.; Gleibs, Ilka H.; Keller, Melanie M.; Froehlich, Laura (Frontiers in Psychology, 2016)
Past research on ethnic composition effects on migrant and ethnic majority students’ performance has reported inconclusive results: Some studies have found no relationship between the proportion of migrant students in school and students’ performance, some revealed positive effects, whereas others showed negative effects of the proportion of migrant students. Most of the studies did not consider whether an increase in the proportion of migrant students in the classroom has different effects on migrant and ethnic majority students’ performance. For this reason, the present study (N = 9215) extends previous research by investigating the cross-level interaction effect of the proportion of Turkish-origin students in classrooms on Turkish-origin and German students’ reading performance with data based on the German National Assessment Study 2008/2009 in the school subject German. In addition, we examined the cross-level interaction effect of Turkish-origin students’ proportion on sense of belonging to school of Turkish-origin and German students, as sense of belonging has been shown to be an important predictor of well-being and integration. No cross-level interaction effect on performance emerged. Only a small negative main effect of the Turkish-origin students’ proportion on all students’ performance was found. As predicted, we showed a cross-level interaction on sense of belonging. Only Turkish-origin students’ sense of belonging was positively related to the proportion of Turkish-origin students: The more Turkish-origin students there were in a classroom, the higher Turkish-origin students’ sense of belonging. German students’ sense of belonging was not related to the ethnic classroom composition. Implications of the results in the educational context are discussed.